1989
DOI: 10.2307/2409583
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Variation in the Parthenogenetic Grasshopper Warramaba virgo and its Sexual Relatives

Abstract: AlIozyme variation was examined within and between parthenogenetic clones of Warramabo virgo and the sexual ancestors, undescribed species PI96 and P169. Both sexual species can be separated into northern and southern races using six loci, and the separate hybrid origin for the two major groups of parthenogenetic clones (the Standard Phylad and the Boulder-Zanthus Phylad) is substantiated by the racial variation in the sexual ancestors. Heterozygosity values in the parthenogenetic species are 6--9 times higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 24 publications
3
36
1
Order By: Relevance
“…Many classical studies showed the expected pattern in almost all putative hybrid unisexual systems known at the time, and they were also, via comparison with allozyme profiles from bisexual species, able to contrast putative parental hypotheses (e.g., Parker and Selander 1976;Vrijenhoek et al 1977;Honeycutt and Wilkinson 1989;Moritz et al 1989;Johnson 1992;Tomiuk and Loeschcke 1992;Bogart and Klemens 1997;Taylor and Ó Foighil 2000). These methods typically detect only a subset of genetic variation, and homology assignment is troublesome, so they were soon superseded by DNA-based techniques that allowed phylogenetic tests of the origins of unisexuality.…”
Section: Introductionmentioning
confidence: 96%
“…Many classical studies showed the expected pattern in almost all putative hybrid unisexual systems known at the time, and they were also, via comparison with allozyme profiles from bisexual species, able to contrast putative parental hypotheses (e.g., Parker and Selander 1976;Vrijenhoek et al 1977;Honeycutt and Wilkinson 1989;Moritz et al 1989;Johnson 1992;Tomiuk and Loeschcke 1992;Bogart and Klemens 1997;Taylor and Ó Foighil 2000). These methods typically detect only a subset of genetic variation, and homology assignment is troublesome, so they were soon superseded by DNA-based techniques that allowed phylogenetic tests of the origins of unisexuality.…”
Section: Introductionmentioning
confidence: 96%
“…Asexual clones arising from a sexual population may each contain only a small sample of the genetic variation within the parent population (Vrijenhoek 1979;Hebert et al 1988;Honeycutt and Wilkinson 1989;Semlitsch et al 1997). The resulting narrower niche for the clones may favour coexistence at local or regional scales (Case 1990;Barata et al 1996;Fox et al 1996;Vrijenhoek and Pfeiler 1997;Negovetic et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of empirical evidence suggests that asexual clones often do represent a limited sample of the genetic variation within sexual populations, and that this constrains the phenotype of each clone to a narrower ecological niche (Vrijenhoek, 1979;Hebert et al, 1988;Honeycutt & Wilkinson, 1989;Semlitsch et al, 1997). There is further evidence to suggest that differences between the biotic or abiotic niches of competing clonal and sexual populations may result in coexistence (Case, 1990;Christensen et al, 1992;Barata et al, 1996;Fox et al, 1996;Vrijenhoek & Pfeiler, 1997;Negovetic et al, 2001).…”
Section: Discussionmentioning
confidence: 99%